PENDIDIKAN KARAKTER DALAM PEMBELAJARAN TAHFIDZ AL QUR’AN DI SDIT IQRA 1 KOTA BENGKULU - Musyanto Musyanto (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
The growth of Islamic educational institutions, specialized Elementary School Islamic increasingly encouraging because these institutions received outstanding in the middle of the city of Bengkulu because the performance and behavior of their students, but on the other hand there are still many remaining problems, many problems occurred in the board- be it educational institutions or public institutions of Islamic education to identify the moral decay that is increasingly; appear in various levels of life be an indicator that the education in Indonesia still need reforms so as to produce students who have good character. One of Integrated Islamic School in Bengkulu that have implemented the 2013 curriculum is integrated Iqra Islamic Primary School 1 in Bengkulu. One of the subjects in which the character is inserted Tahfidz Koran lessons. The school has provided one of the shape and pattern of character education in learning Tahfidz Qur'an enter 5 characters are: Religious, clean, constancy, discipline, andpatience "in studies.Tujuan this study is 1. To know the educational measures Tahfidz learning characters in the Qur'an. 2. The implementation of character education in Tahfidz learning the Qur'an. 3. To learn evaluation Tahfidz character education in learning the Qur'an in Islamic primary schools integrated IQRA 1. Data analysis in this research is the analysis of qualitative data, where data analysis is performed interactively and continues over at every stage of research until and its data until thoroughly saturated. Data collection was conducted through observation, interviews and documentation.